2022
DOI: 10.34172/joddd.2022.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retention and denture base adaptation between conventional and 3D-printed complete dentures

Abstract: Background. In recent years, complete denture construction has been revolutionized using computer-aided designing and computer-aided manufacturing (CAD-CAM) technology. This clinical study compared the retention and denture base adaptation of 3D-printed complete dentures fabricated using dimethacrylate-based resins with a photoinitiator versus conventional complete dentures. Methods. Ten completely edentulous patients were nominated for this study. Each patient received two complete dentures. One complete dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Two clinical crossover studies were found that compared clinical parameters of 3D-printed complete removable dental prostheses (CRDPs), such as adaptation, retention, and occlusal forces. One study found no significant differences for adaptation or retention between the conventional and 3Dprinted dentures, 43 while the second study found differences in the occlusal schemes, with the printed one having less favorable distribution. 44 An important potential benefit of a CAD/CAM denture base is the ability to decrease the thickness while maintaining clinically acceptable mechanical properties.…”
Section: Complete Removable Dental Prosthesesmentioning
confidence: 92%
“…Two clinical crossover studies were found that compared clinical parameters of 3D-printed complete removable dental prostheses (CRDPs), such as adaptation, retention, and occlusal forces. One study found no significant differences for adaptation or retention between the conventional and 3Dprinted dentures, 43 while the second study found differences in the occlusal schemes, with the printed one having less favorable distribution. 44 An important potential benefit of a CAD/CAM denture base is the ability to decrease the thickness while maintaining clinically acceptable mechanical properties.…”
Section: Complete Removable Dental Prosthesesmentioning
confidence: 92%
“…The conventional protocol for fabricating a mucosa-supported prosthesis involves a lengthy sequence of clinical and laboratory steps, which can result in a relatively long time period for completion. The polymerization shrinkage of polymethyl methacrylate (PMMA) and the difficulty in duplicating the prosthesis in case of a need to revert to earlier manufacturing stages can be considered the main drawbacks of the technique [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%